(untitled) (Vojnotehnički glasnik / Military Technical Courier, 2022)
Pursuant to the Regulations on categorization and ranking of scientific journals (Official Gazette of the Republic of Serbia, No 159/20), the Ministry of Education, Science and Technological Development of the Republic of Serbia classified the Military Technical Courier for the year 2021, on December 23, 2021.